Macroeconomic indicators in foreign exchange rate volatility: A case in China / Nur Farah Izzati A. Aziz - A. Aziz, Nur Farah Izzati (Faculty of Business and Management, 2018)
The volatility of the exchange is outlined because. the risk associated with sudden movements in exchange rates. High volatility means that the price of the currency can change drastically in a short period of time in both directions. On the other hand, lower volatility would mean that an exchange rate does not fluctuate dramatically, but changes its value at a constant rate over a period of time. China is the one of the largest trade centre in the world after the United States. But prices fluctuate more than 10 percent in one day. This makes it one of the most volatile in the world. It is so volatile because individual investors who are new on the market account for over 80% of transactions. China directly influences the US dollar by linking the value of its currency, the yuan, to the dollar. The Chinese monetary power derives from its numerous exports to the United States. The main categories are consumer electronics, clothing and machinery. In addition, many US companies send raw materials to Chinese factories to make low-cost assemblies. The finished products are considered as imports when the factories send them to the United States. This is how the US trade deficit with China is profitable for US companies. The focus of this study is on the macroeconomic indicators that give direct and indirect influence towards the exchange rate movements in China. Macroeconomic variables such as interest rates, inflation, exports, gross domestic product (GDP) and external debt are the random effect of exchange rates. This research study investigates the impact of exchange rate volatility in China based on annual data from 1987 to 2017, which was obtained from DataStream Thomson Reuters.